2010
DOI: 10.1007/s00213-010-1999-0
|View full text |Cite
|
Sign up to set email alerts
|

Biological aspect of hyperthymic temperament: light, sleep, and serotonin

Abstract: The present findings suggest that light, sleep, and serotonin are crucial factors in understanding hyperthymic temperament, which may be common to bipolar disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 31 publications
1
12
0
1
Order By: Relevance
“…More importantly, Hoaki et al (2011) reported that the greater illuminance of daytime independently predicted higher hyperthymic temperament scores via a multiple regression analysis. That study measured the illuminance that each participant received using actigraphy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, Hoaki et al (2011) reported that the greater illuminance of daytime independently predicted higher hyperthymic temperament scores via a multiple regression analysis. That study measured the illuminance that each participant received using actigraphy.…”
Section: Discussionmentioning
confidence: 99%
“…This interesting "latitude effect" on affective temperaments was recently confirmed by our subsequent extension study of three regions with different latitudes that indicated a dose-response relationship between hyperthymic temperament and sunshine and latitude (Kohno et al, 2014) (our unpublished data). Hoaki et al (2011) reported that more hyperthymic participants receive more light. In addition, more hyperthymic participants prefer brightness and dislike darkness compared with less hyperthymic participants, suggesting the presence of heliotropism (Harada et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…
We greatly appreciate Emeritus Professor Kripke for his interest in our recent article (Hoaki et al 2010) where it was revealed that higher illuminance of daytime, greater fluctuation in sleep time, and lower central serotonergic function significantly and independently predicted hyperthymic tendency.In response to the inquiry from Emeritus Professor Kripke, we investigated the association between illuminance of daytime and Hamilton depression rating scale (HAM-D) scores and that between illuminance of daytime and Young mania rating scale (YMRS) scores. As a result, there was a significantly negative association between illuminance of daytime and Hamilton depression rating scale scores (rho=−0.23, p=0.035), but no significant association between illuminance of daytime and YMRS.
…”
mentioning
confidence: 98%
“…We greatly appreciate Emeritus Professor Kripke for his interest in our recent article (Hoaki et al 2010) where it was revealed that higher illuminance of daytime, greater fluctuation in sleep time, and lower central serotonergic function significantly and independently predicted hyperthymic tendency.…”
mentioning
confidence: 98%
“…These data suggest that some temperamental profiles and/or association of temperamental traits may condition the more or less early occurrence of comorbidities which could themselves constitute risk factors for the further development of affective disorders. For instance, individuals carrying the S allele of the serotonin transporter gene, show high concentration of serotonin in the synaptic cleft and are frequently found among subjects with depressive temperamental traits [67] and/or those with heightened anxiety [68]; in contrast individuals with hyperthymic temperament seem to be characterized by lower central serotonergic function [69] and overrepresented among ADHD patients [70]. Moreover the L allele of the serotonin transporter gene was shown to be a risk factor for the development of ADHD [71].…”
Section: Discussionmentioning
confidence: 97%